Development of the Flour-milling Industry in the Republic of Kazakhstan in Modern Times - Altaibaeva, Zhanat; Bauer-Kenzhebolatova, Maira; Zhaltyrova, Olga (International Journal of Economics and Financial Issues, 2016)
The article presents flour production behavior in the Republic of Kazakhstan, flour export by countries, wheat flour and bread prices. The authors have analyzed the raw materials base of the flour-milling industry (acreage, yield, crop page). Flour is the most important grain-processing product. It is a raw material for the production of such irreplaceable foodstuffs as bread, bake and paste goods that meet an essential part of human daily needs in vital energy and nutrients. Kazakhstan has a substantial grain and flour export potential. Flour export is important for the grain industry of the Republic, and economy of the country in whole. The country ranks among the six biggest grain exporters in the world. This is because Kazakhstani grain has high milling property, and the quality of Kazakhstani flour is rated high in many countries. It enables Kazakhstani flour to be competitive on the world market and to ensure end markets in different countries. Kazakhstani flour is exported mainly to Uzbekistan, Afghanistan and Tajikistan (90-92% of flour export). A part of local flour is exported to Kirgizia, Turkmenistan and Mongolia. Kazakhstan rapidly develops its grain-processing industry. Grain processing means not only flour production, it includes motor and railway transport, internal and external commercial operations, electricity consumption, etc. The authors present priorities and solutions for the flour-milling industry. Keywords: flour, grain, production, sale, price, export, processing, bread JEL Classifications: D24, D40, F19, L66